IMPLEMENTING NEUROSCIENTIFIC PRINCIPLES IN EARLY CHILDHOOD EDUCATION: A CASE STUDY OF TKIT UMAR BIN KHATHAB KUDUS - hasanah, Uswatun; Isnawati, Zakiyah (THUFULA, 2024)
An early childhood education teacher must possess adequate knowledge and skills in early childhood pedagogy to ensure that the learning process is effective and efficient. This study aims to reveal teaching techniques that incorporate neuroscientific insights to enhance children’s ability to absorb the information provided during lessons at TKIT Umar Bin Khathab Kudus. The research methodology employed is descriptive and qualitative, with data collection conducted through observation, interviews, and documentation. The study participants include a principal, two teachers, 30 students from class B, and two parents. After data collection, the study analyzes the data by relevant theories. The results indicate that the teaching at TKIT Umar Bin Khathab Kudus has adopted neuroscience principles by implementing center-based methods. Teachers’ skills in initiating lessons have been observed during the pre-exposure and preparation stages. Furthermore, teachers have conducted the stages of initiation, acquisition, elaboration, and memory incubation in explaining the learning material. Finally, in concluding the learning process, teachers have applied the stages of verification, comprehension checking, celebration, and integration. The teaching skills applied are reflected in the improvement of students’ learning outcomes on each indicator.